PERTUMBUHAN AKAR PADA PERKECAMBAHAN BEBERAPA VARIETAS TOMAT DENGAN PEMBERIAN POLYETHYLENE GLIKOL (PEG) SECARA IN VITRO - Erni Royani Harahap; Luthfi Aziz. M Siregar; Eva Sartini Bayu (Jurnal Agroekoteknologi, 2013)
Tomato plants originated from Mexico to Peru region. At the present time the tomato hasbecome more developed, modern cultivars or hybrids can grow well and produce the climate ismuch different from the place of origin. This study aims to create drought tolerant plant of tomatovarieties. The research has done in Tissue Culture Laboratory Fakultuty Agriculture UnivercityNort Sumatera, Medan since Juli-September 2012. Using a completely randomized design with twofactors, that is Polyethylene Glicol (PEG) (0,5,10,15,20%) and Tomato varieties (TO-244, Niki,Kartika, Mio, Super Hawai) with four replications. Observation variable is living root forminginitiation, total of root, and high of roott. The result of research has shown that PEG is significantfor root forming initiation and high of root, but not significant for total of root.